2020
DOI: 10.1038/s41598-020-62008-9
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of combined free nitrous acid and Fenton technology in enhancing anaerobic digestion of actual sewage waste activated sludge

Abstract: in this study, actual swage waste activated sludge in batch reactors was employed to assess the synergistic effect of free nitrous acid and Fenton pre-treatments on enhancing methane production in the anaerobic digestion process. in addition to methane enhancement, the mechanisms driving the enhancement were also investigated via measuring enzymes activity and solubilisation of organic matter. This study revealed that the combined pre-treatments solubilised organic matter significantly more than the bioreactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…To evaluate the biomethane produced per kg of organic matter added, SMP was also evaluated in each batch, the evolution of which is shown in Figure 2b. Although there are no SMP data available in the literature on the triple AcoD of SS:WDW:CM for the sake of comparison, the results (200− 230 L CH 4 /kg VS) appear to be appropriate as they are in line with previous studies on AD of SS (between 200 and 250) 26,28,40 and CM (230−260 L CH 4 /kg VS) 5,41 and AcoD of SS:WDW (230 L CH 4 /kg VS). 18 According to Figure 2b, a slight increase (7−16%) can be observed when CM was used as a cosubstrate.…”
Section: Methodssupporting
confidence: 69%
See 2 more Smart Citations
“…To evaluate the biomethane produced per kg of organic matter added, SMP was also evaluated in each batch, the evolution of which is shown in Figure 2b. Although there are no SMP data available in the literature on the triple AcoD of SS:WDW:CM for the sake of comparison, the results (200− 230 L CH 4 /kg VS) appear to be appropriate as they are in line with previous studies on AD of SS (between 200 and 250) 26,28,40 and CM (230−260 L CH 4 /kg VS) 5,41 and AcoD of SS:WDW (230 L CH 4 /kg VS). 18 According to Figure 2b, a slight increase (7−16%) can be observed when CM was used as a cosubstrate.…”
Section: Methodssupporting
confidence: 69%
“…The characteristics of the raw cosubstrates are shown in Table and fall within the usual range reported in the literature. ,, …”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…A combination of 2.5 mg N/L FNA, 50 mg H2O2/g TS and 0.0067 g Fe + /g H2O2 was retained for a total of 6 hours (5 hours for FNA at pH 5.5, 1 hour Fenton at pH 3) and increased the fraction of rBOM in mixed sewage sludge by more than 113% times compared to the sole FNA treatment and 87% more than the sole Fenton treatment (Karimi et al, 2020). Methane production from the pretreated sludge was 69% more than obtained from the untreated sludge.…”
Section: Free Nitrous Acid Treatment In Water Resource Recovery Facil...mentioning
confidence: 99%
“…Wang et al (2018) concluded that FNA induces the permeabilization of bacteria and may lead to cell membrane lysis [2]. Despite the lack of a complete understanding of the mechanism, many studies have proven the effectiveness of NO 2 /FNA as a WAS disintegration agent in terms of soluble chemical oxygen demand (SCOD) release, and consequently for increased methane production [12][13][14]. Ma et al showed that FNA pretreatment of WAS (concentrations up to 2 mgN-HNO 2 /L) enhanced the exploitation of internal carbon sources during the simultaneous fermentation denitrification process.…”
Section: Introductionmentioning
confidence: 99%